Gender in the NDCs: Towards Transformation - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Produced as part of the Gender Platform/FAO project “Conducting a Global Policy Review of the Nexus of Climate Change and Gender & Development of a Compendium of Best Practices around Gender and Climate Change Policies & Four Thematic Notes”.